The Influence of Accounting Information System Usage on the Performance of SME in Medan Krio Village, Indonesia - Nababan, Jesika; Gaol, Vebry M. Lumban; Munte, Mei Hotma Mariati (Manunggal Halim Jaya, 2025)
This study examines the effect of using Accounting Information Systems (AIS) on the performance of SME in Medan Krio Village, Sunggal District. The method used is quantitative, with a survey approach through questionnaires to 162 SME actors, which were analyzed using simple linear regression. The results showed that the use of AIS had a significant and positive effect on the performance of SME, with an influence contribution of 71.5%. This finding confirms that adopting accounting technology can improve operational effectiveness, reporting accuracy, and strategic decision-making in SME. In conclusion, accounting information systems are an essential tool in supporting the sustainability of SME, and it is recommended that the government and stakeholders encourage training and access to this technology for small businesses in the region. Further research could explore other variables that influence SME.